Rapid Detection of Tetracycline Residues in Chicken - Patrabansh, Shraddha; Parajuli, Niranjan; Jha, Vinay Kumar (International Journal of Applied Sciences and Biotechnology, 2020)
Antibiotic residues in meat are a serious public health concern as a result of its harmful effects on consumer health. This study aimed at estimating the residues levels of commonly used antibiotics (Tetracycline) in chicken samples using two analytical methods; Rapid Screening Kit and HPLC. Twenty chicken samples were collected from various meat shops of Kathmandu valley. Qualitative and semi-quantitative analyses with Quicking Tetracycline rapid Test kit, which detect tetracycline above 100 ppb in tissue revealed that two samples were positive for antibiotic residues in the chicken for tetracycline. The concentration of residues of tetracycline, which were positive in rapid test kit was quantified by high-performance liquid chromatography equipped with a UV detector (HPLC-UV). One muscle sample and one liver sample of chicken have found the concentration of tetracycline as 229 and 339 μg/kg, respectively while chlortetracycline was not detected. This result confirmed widespread misuses of antibiotics especially tetracycline in farm and lack of application of recommended withdrawal times. Antimicrobial assay of chicken extracts was also performed by using the disc-diffusion agar method. The plates were incubated overnight at 37 °C for 18-24 hours, but microbial growth was not observed in all the samples tested. Int. J. Appl. Sci. Biotechnol. Vol 8(1): 14-20